Comparative analysis of the results of multigrade and singlegrade classes based on indicators of educational productivity and efficiency: A case study of Bandar Abbas city primary and secondary schools - Vahid Motamedi; Fateme Khajouie (Intelektual Pustaka Media Utama, 2020)
Research on multigradein comparison to singlegradeclasses often overlooksthe issues and challenges facing the nation's educational authorities in administering these classes. The purpose of this study was to compare multi and singlegrade classes in terms of educational efficiency and effectiveness. The population of this study consisted of all students, parents, teachers and principals of schools in Bandar Abbas city in the academic year 2017-18. A researcher-made questionnaire was used to collect educational productivity data. The findings of the study showed that there was no significant difference between self-esteem of the two groups of students but in terms of social skills and social development, students in the multigrades classes were better off. In terms of educational efficacy, singlegrade student's survival rate was better but there was no significant difference between the two groups in terms of promotion and repetition rate.